Fibroblast growth factor 21 increases hepatic oxidative capacity but not physical activity or energy expenditure in hepatic peroxisome proliferator‐activated receptor γ coactivator‐1α‐deficient mice. Issue 3 (16th January 2018) - Fletcher, Justin A.; Linden, Melissa A.; Sheldon, Ryan D.; Meers, Grace M.; Morris, E. Matthew; Butterfield, Anthony; Perfield, James W.; Rector, R. Scott; Thyfault, John P.
Abstract : New Findings: What is the central question of this study? Does a reduction in hepatic peroxisome proliferator‐activated receptor γ coactivator‐1α (PGC‐1α), which has been observed in an insulin‐resistant obese state, impair the ability of fibroblast growth factor 21 (FGF21) to modulate metabolism? What is the main finding and its importance? A deficit in hepatic PGC‐1α does not compromise the ability of FGF21 to increase hepatic fatty acid oxidation; however, the effects of FGF21 to regulate whole‐body metabolism (i.e. total and resting energy expenditure), as well as ambulatory activity, were altered when hepatic PGC‐1α was reduced. Abstract: Fibroblast growth factor 21 (FGF21) treatment drives metabolic improvements, including increased metabolic flux and reduced hepatic steatosis, but the mechanisms responsible for these effects remain to be elucidated fully. We tested whether a targeted reduction in hepatic peroxisome proliferator‐activated receptor γ coactivator‐1α (PGC‐1α), which has been shown to occur with obesity, had a negative impact on the metabolic effects of FGF21. We infused FGF21 (1 mg kg −1  day −1 ) or saline in chow‐fed wild‐type (WT) and liver‐specific PGC‐1α heterozygous (LPGC‐1α) mice for 4 weeks. Administration of FGF21 lowered serum insulin and cholesterol ( P  ≤ 0.05) and tended to lower free fatty acids ( P  = 0.057). The LPGC‐1α mice exhibited reduced complete hepatic fatty acid oxidation (FAO; LPGC‐1α, 1788 ± 165 nmol g −1  h −1 compared with WT, 2572 ± 437 nmol g −1  h −1 ; P  < 0.001), which was normalized by FGF21 treatment (2788 ± 519 nmol g −1  h −1 ; P  < 0.001). FGF21 also increased hepatic incomplete FAO by 12% in both groups and extramitochondrial FAO by 89 and 56% in WT and LPGC‐1α mice, respectfully ( P  = 0.001), and lowered hepatic triacylglycerol by 30–40% ( P  < 0.001). Chronic treatment with FGF21 lowered body weight and fat mass ( P  < 0.05), while increasing food consumption ( P  < 0.05), total energy expenditure [7.3 ± 0.60 versus 6.6 ± 0.39 kcal (12 h) −1 in WT mice; P  = 0.009] and resting energy expenditure [5.4 ± 0.89 versus 4.6 ± 0.21 kcal (12 h) −1 in WT mice; P  = 0.005]. Interestingly, FGF21 only increased ambulatory activity in the WT mice ( P  = 0.03), without a concomitant increase in non‐resting energy expenditure. In conclusion, although reduced hepatic PGC‐1α expression was not necessary for FGF21 to increase FAO, it does appear to mediate FGF21‐induced changes in total and resting energy expenditure and ambulatory activity in lean mice. Abstract :